The Impact of Personality Trait on Final-Year Students’Flourishing: A Path-Analysis Approach - Mahmudah, Arifah Nur; Darmayanti, Kusumasari Kartika Hima (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
An individual’s personality influences flourishing. Therefore, this study purposed to determine the influence of personality traits on the flourishing of final-year students. This data was collected using the PERMA-Profiler and Big Five Inventory. This study was a quantitative study with a non-experimental research design. The sampling technique used purposive sampling on 300 final-year students. The data analysis method was multiple linear regression techniques assisted by the Jamovi 2.3.18. The findings showed that the significant five personality effect flourished by R2 = 32,2%. In addition, it was found that agreeableness was the most influential variable in the flourishing of final-year students, followed by conscientiousness and extraversion. On the other hand, this study confirmed that openness and neuroticism had no significant effect on flourishing. The results contributed to interventions from the university to pay attention to agreeableness, conscientiousness, and extraversion to develop flourishing in final-year students.